ChemInform Abstract: Classical and Nonclassical Germanium Environments in High‐Pressure BaGe5. Issue 16 (April 2015) - Castillo, Rodrigo; Carrillo‐Cabrera, Wilder; Schwarz, Ulrich; Grin, Yuri
Abstract The high‐pressure modification of BaGe5 is obtained from a 1:5 molar mixture of Ba6Ge25 and Ba (multianvil press, 15 GPa, 1000‐1200 K, 2 h).